Spatiotemporal variation and ecological risk assessment of sediment heavy metals in two hydrologically connected lakes - Jiang, Mengyu; Wang, Qichen; Tian, Xue; Zhu, Xiaoyan; Dong, Xiangqian; Wu, Zhong; Yuan, Yuxiang (Frontiers in Ecology and Evolution, 2022)
Excessive accumulation of heavy metals in global lake sediments poses a serious threat to lake water quality and ecosystem security. However, there is still a knowledge gap in comparison of heavy metal variation and pollution in hydrologically connected lakes. In this study, concentrations of As, Cd, Cr, Cu, Hg, Pb, and Zn in sediments of two hydrologically connected lakes, Xingkai Lake and Xiaoxingkai Lake, were determined during the hydrologically connected periods (May and September) and disconnected period (January and July) in 2021. We found the range of As was 2.58 ~ 14.35 mg/kg, Cd was 0.050 ~ 0.21 mg/kg, Cr was 28.58 ~ 262.3 mg/kg, Cu was 3.12 ~ 28.05 mg/kg, Hg was 0.0030 ~ 0.14 mg/kg, Pb was 10.87 ~ 58.86 mg/kg, and Zn was 18.21 ~ 90.73 mg/kg. Heavy metal concentrations were lower than grade I level in Chinese soil quality standards with significant spatial and temporal differences in the basin. Overall, most of the sampling sites in Xingkai Lake and Xiaoxingkai Lake were at the uncontaminated level and moderate ecological risk during the sampling period. Two lakes showed different heavy metal compositions, accompanied by higher contamination level and higher potential ecological risk in the small lake than those in the large lake based on analysis of the geo-accumulation index and potential ecological risk index. Besides, the contamination level and potential ecological risk in May and September were higher than those in January and July, mainly due to human activities and hydrological connectivity. The ecological risks were moderate for Cd and Hg, and low for As, Cr, Cu, Pb, and Zn. Correlation and PCA analyses showed that Cd mainly originated from anthropogenic sources, while other metals mainly came from natural sources. These findings elucidate the effects of agriculture and hydrological connectivity on heavy metals in sediments, and provide scientific basis for the reasonable management of lake ecosystem.